2008
DOI: 10.1016/j.nuclphysa.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matter in the chiral limit and the in-medium chiral condensate

Abstract: We investigate nuclear matter, i.e. the nuclear equation-of-state (EOS) as well as the relativistic mean fields in the chiral limit. The investigations are based on a chiral nucleon-nucleon EFT interaction where the explicit and implicit pion mass dependence is known up to next-to-leading order. The nuclear bulk properties are found to remain fairly stable in the chiral limit. Based on the same interaction the in-medium scalar condensate is derived, both in Hartree-Fock approximation as well as from the Brueck… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 64 publications
6
11
0
Order By: Relevance
“…Note that we obtain a realistic equation of state for symmetric nuclear matter and the quark condensate keeps its trend to vanish for higher densities, as also observed in ref. [32]. We agree on the observation performed in refs.…”
Section: Discussion and Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Note that we obtain a realistic equation of state for symmetric nuclear matter and the quark condensate keeps its trend to vanish for higher densities, as also observed in ref. [32]. We agree on the observation performed in refs.…”
Section: Discussion and Resultssupporting
confidence: 93%
“…We agree on the observation performed in refs. [30,32] that the short-range nucleon-nucleon interactions effects are suppressed for the evaluation of the in-medium quark condensate which is dominated by long-ranged pion physics. This is a consequence of eq.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…(14), actually explain observations made in earlier calculations [16,17] about the dominant role of the long-range part of nucleon interactions for the inmedium chiral quark condensate. In the previous equation the second and third term on the right hand side rise from diagram 1 and the last term, which represents the quark mass derivative of the nuclear matter energy density, is identified with diagrams 3 and 6.…”
Section: In-medium Chiral Quark Condensatesupporting
confidence: 64%
“…Employing a recent computation of the NN-potential in lattice QCD [7] (at three different pion masses) we have found that the contact term has a negligible influence on the in-medium quark condensate (in agreement with ref. [8] which follows a somewhat different approach). As a result, we have obtained in ref.…”
Section: Introduction and Frameworkmentioning
confidence: 99%